The Effect Of Pre-Treatment On Octenyl Succinic Anhydride (Osa)-Modified Potato Starch In Stabilizing Pickering Emulsion - Lim, Xiao Xian (2020)
Potato (Solanum tuberosum) starch, one of the most abundant natural materials that can be easily obtained at a low cost, is found suitable to be used as a particle in stabilizing Pickering emulsion. However, native starch is not hydrophobic in nature and has limited water solubility, thus restricting its function as an emulsifier. The hydrophobicity of starch is commonly enhanced using Octenyl Succinic Anhydride (OSA)-modification. However, only 3 % treatment is permitted by The United States Food and Drug Administration (FDA) which usually resulted in low emulsifying properties